LEGAL PROTECTION FOR WORKERS IN SPECIFIC TIME WORKING AGREEMENTS (PKWT) IN INDOLIMA PERKASA - Rifani Anindhika Sari; Hamza Baharuddin; Zainuddin (P3M Stia Al Gazali Barru and Meraja media, 2020)
[Full Paper] to pdf Copyright (c) 2020 Meraja journal